'What's in a Name?' Taxonomic Choices in the Field of Dance Studies. (May 2021) - Mollenhauer, Jeanette
Abstract : Dance genres sometimes require categorisation and this article addresses a collective for which no universally-accepted terminology has been located. Using the example of the author's doctoral research in Australia, four alternatives are examined in turn: 'folk', 'ethnic', 'world' and 'traditional', with analysis of the advantages and problems embedded in each term. Discussion of the Australian social and political environment exemplifies pertinent location-specific issues that need to be addressed when making taxonomic choices. The article aims to stimulate further discursive commentary and encourage epistemological and linguistic clarity among dance scholars.